2019
DOI: 10.1016/j.joen.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices of Family and Emergency Physicians in Managing Nontraumatic Dental Conditions: A Case-based Survey

Abstract: Background:Physicians are often patients' first point of contact for management of nontraumatic dental conditions (NTDCs). Objective: To evaluate the knowledge and practices of Ontario physicians in managing NTDCs. Methods: A scenario-based online survey was distributed to Ontario family and emergency physicians (n = 1012). Descriptive and logistic regression analyses were performed. Results: 204 surveys were completed (20.2% response rate). A majority of the sampled physicians would prescribe antibiotics for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 187 publications
(459 reference statements)
0
2
0
Order By: Relevance
“…25 General physicians should get a proper education and knowledge before they can take up a broader role in the early diagnosis of oral diseases. 26 Failure of examination of the oral cavity which includes teeth and its supporting structures by physician has been reported. 27 So it should be encouraged to do routine oral examination of patients with uncontrolled diabetes who are at higher risk for developing periodontal disease.…”
Section: Methodsmentioning
confidence: 99%
“…25 General physicians should get a proper education and knowledge before they can take up a broader role in the early diagnosis of oral diseases. 26 Failure of examination of the oral cavity which includes teeth and its supporting structures by physician has been reported. 27 So it should be encouraged to do routine oral examination of patients with uncontrolled diabetes who are at higher risk for developing periodontal disease.…”
Section: Methodsmentioning
confidence: 99%
“…With a 20.2% response rate from 1012 physicians, the study found that 57.4% of physicians prescribed antibiotics for irreversible pulpitis articles, with amoxicillin being the most prescribed antibiotic. This research provided insights into antibiotic prescription practices followed by physicians in Ontario when addressing dental conditions [36].…”
Section: Individual Study Findingsmentioning
confidence: 99%